2021
DOI: 10.3390/w13162231
|View full text |Cite
|
Sign up to set email alerts
|

Wood Retention at Inclined Bar Screens: Effect of Wood Characteristics on Backwater Rise and Bedload Transport

Abstract: In forested mountain catchment areas, both bedload and large wood (LW) can be transported during ordinary flows. Retention structures such as sediment traps or racks are built to mitigate potential hazards downstream. Up to now, the design of these retention structures focuses on either LW or bedload. In addition, the majority of LW retention racks tend to retain both LW and bedload, while bedload transport continuity during ordinary flows is an important aspect to be considered in the design. Therefore, a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…For larger grains, the features specific to elongated grains are further amplified when surrounded by a fluid [26], but the extent to which they affect the mobility of granular flows is yet poorly understood, especially in the immersed case. The latter is, for example, of great interest in understanding the jamming of driftwood debris [46,54,55] or in the stability of layered cliffs which can result from debris or pyroclastic flows [42,73], where the collective orientation of its constituent grains plays a dominant role in the process.…”
Section: Introductionmentioning
confidence: 99%
“…For larger grains, the features specific to elongated grains are further amplified when surrounded by a fluid [26], but the extent to which they affect the mobility of granular flows is yet poorly understood, especially in the immersed case. The latter is, for example, of great interest in understanding the jamming of driftwood debris [46,54,55] or in the stability of layered cliffs which can result from debris or pyroclastic flows [42,73], where the collective orientation of its constituent grains plays a dominant role in the process.…”
Section: Introductionmentioning
confidence: 99%
“…Schalko et al. (2021) highlighted the negligible importance of LW shape (e.g., rootwads and branches) on both backwater rise and bedload retention. Welber et al.…”
Section: Introductionmentioning
confidence: 99%
“…Among the few studies that have been conducted so far, Schmocker and Hager (2011) demonstrated that, under steady flow conditions, the blocking probability for both simple logs and logs with rootwads decreases with an increasing Froude number. Schalko et al (2021) highlighted the negligible importance of LW shape (e.g., rootwads and branches) on both backwater rise and bedload retention. Welber et al (2013) explored the characterization of LW deposition patterns, linked to LW characteristics (e.g., rootwads), flow rate, and bed morphology.…”
mentioning
confidence: 99%
“…Schalko et al [21] present flume experiments to study the effect of LW accumulations at an inclined bar screen with a bottom clearance on backwater rise and bedload transport. The main focus was put on testing different LW characteristics.…”
mentioning
confidence: 99%